Effect of Antioxidant Supplementation in Freezing Extender on Porcine Sperm Viability, Motility and Reactive Oxygen Species - Sang-Hyoun Park; Il-Jeoung Yu (The Korean Society of Animal Reproduction and Biotechnology, 2017)
The present study was aimed to determine the effect of green tea extract (GTE) and beta-mercaptoethanol (β-ME) supplementation in boar sperm freezing extender on sperm motility, viability and reactive oxygen species (ROS) level. Experimental groups were allocated into Lactose-egg yolk (LEY) without antioxidant (control), GTE (1,000 mg/L GTE in LEY) and β-ME (50 μM β-ME in LEY). Spermatozoa extended with LEY were cooled to 5°C for 3 h and then kept at 5°C for 30 min following dilution with LEY containing 9% glycerol and 1.5% Equex STM (final sperm concentration: 1 × 108/mL). Spermatozoa were loaded into straws and frozen in nitrogen vapor for 20 min. Following thawing at 37°C for 25 sec, sperm viability and ROS level were measured using fluorescent double stain Fertility? and cytometry, respectively. Motility and viability of GTE supplemented-group were higher than those of control and β-ME without significance. ROS level in GTE group showed significantly lower than control (P < 0.05). In conclusion, GTE supplementation in boar sperm freezing extender can reduce ROS generation during freezing.